Syllables in TİD - Kadir Gökgöz (Dilbilim Araştırmaları Dergisi)
We have two aims in this paper. Our first aim is to show that syllables exist in TİD prosody (Türk İşaret Dili – Turkish Sign Language). A specific domain in prosody is substantiated only if there are phonological phenomena that refer to that domain as part of their definition. Therefore, for our first aim, we present evidence from phonological phenomena which need to refer to the notion syllable in their definition. As for these phenomena, we present Fingerspelling of one-handed suffixes which are restricted to a single syllable size in their lexicalized form. We also present some compounds which are reduced to a single syllable size while the lexemes before compounding form separate syllables. Next, as a case of phonological fusion, Coalescence will be shown to be limited to a single syllable size. These three phonological phenomena are domain processes which, to be defined, need the entire domain of syllable. We also show two phonological phenomena that need to refer to the edges of a syllable. These are Metathesis and Backwards Signing in both of which the order of the initial and final edges of the syllable are reversed. To support the existence of a prosodic domain, it is important to show that the specific prosodic domain is independent - it is not isomorphic to a morphological or a syntactic domain (Nespor and Vogel, 2007). Therefore, our second goal is to show that syllables are independent of two other units in grammar - Morpheme and Sign - by illustrating differences between them. We finish this paper by summary and indicating potential topics of study.